2016
DOI: 10.1016/j.addbeh.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with benzodiazepine use among people who inject drugs in an urban Canadian setting

Abstract: Background Though known to have abuse potential, benzodiazepine medications remain widely prescribed. Furthermore, issues related to benzodiazepine use by people who inject drugs (PWID) remain to be fully characterized. We therefore sought to examine the prevalence of and risk factors associated with benzodiazepine use in a street-involved urban population. Methods Between May 1996 and November 2013, data were derived from two open prospective cohort studies in Vancouver, Canada, restricted to PWID. Multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…Other studies also indicate a benzodiazepine-using population that engages in polysubstance use (Kurtz et al, 2011; Tucker et al, 2016) and is largely non-Hispanic White (Chen et al, 2011; McCabe, 2005; McCabe & West, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Other studies also indicate a benzodiazepine-using population that engages in polysubstance use (Kurtz et al, 2011; Tucker et al, 2016) and is largely non-Hispanic White (Chen et al, 2011; McCabe, 2005; McCabe & West, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…For those who misuse opioids, benzodiazepine use has been associated with being white (Cropsey et al, 2015; Tucker et al, 2016); being female (Cropsey et al, 2015; Stein et al, 2017b); older age (Stein et al, 2017b); and incarceration history (Tucker et al, 2016). Non-medical benzodiazepine use has been associated with screening positive for anxiety, depression, and other mental health concerns in this population (Chen et al, 2011; Lavie et al, 2009).…”
Section: 0 Introductionmentioning
confidence: 99%
“…The variables considered as potential predictors of TM initiation were selected based on the literature [11,13,18,19,[21][22][23][24][25][26][27][28].Potential factors explored were age (older individuals defined as >25-years-old vs. younger ones) [32], sex, country of origin (born in Canada vs. outside) and education (high school completed vs.non-completed). Main residential status (homelessness vs. stable residence), having a criminal activity as the main source of income (i.e.…”
Section: Variablesmentioning
confidence: 99%
“…Among persons who use drugs (PWUD), research on the use of tranquilizers has mainly concentrated on benzodiazepines. Studies have shown that benzodiazepine use (including misuse) is widespread among opiate users, including methadone-maintained individuals and active heroin users [6][7][8][9][10][11][12], persons who inject drugs (PWID) [13][14][15][16][17][18] and amphetamine users [19]. In Canada, data from the I-Track surveillance system reveals that between 2005 and 2008, 35.2% of PWID had used benzodiazepines by non-injection route of administration in the 6 months prior to the interview [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation